Eficácia executiva da sentença declaratória - Dias, Luana Mariah Fiuza (2020)
This paper aims to evaluate the executive effectivess of non-condemnatory sentences, with the implementation of the law as a reflex effect of the decision, in order to guarantee legal certainty, effectiveness and satisfaction. The double character of jurisdictional protection and the preclusive efectivess of questiono of possible dispute over the object of the dispute will be analyzed, avoiding the eternalization of judicial demands. Thus, in the end, in a systematic analysis oh the legal system, verify the possibity of conferring materialization and satisfaction os the right for all jurisdictional tutelages, if surch phenamon is authorized